2022
DOI: 10.1007/s44211-022-00253-w
|View full text |Cite|
|
Sign up to set email alerts
|

Separation of long-stranded RNAs by RP-HPLC using an octadecyl-based column with super-wide pores

Abstract: Messenger ribonucleic acids (mRNAs) have been used in vaccines for various diseases and are attracting attention as a new pharmaceutical paradigm. The purification of mRNAs is necessary because various impurities, such as template DNAs and transcription enzymes, remain in the crude product after mRNA synthesis. Among the various purification methods, reversed-phase high-performance liquid chromatography (RP-HPLC) is currently attracting attention. Herein, we optimized the pore size of the packing materials, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…10,18 Regarding the analysis of long mRNAs, Kuwayama et al reported the interest in using an octadecyl-based RPLC column with superwide pores for achieving higher separation. 19 Similarly, an ultrawide pore size exclusion chromatography (SEC) column has been recently introduced for efficient separation of mRNA aggregates and lipid nanoparticles. 20 Additionally, mass photometry (MP) was recently introduced as an interferometric mass spectrometry (MS) methodology capable of measuring the mass and relative abundance of biomolecules in solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18 Regarding the analysis of long mRNAs, Kuwayama et al reported the interest in using an octadecyl-based RPLC column with superwide pores for achieving higher separation. 19 Similarly, an ultrawide pore size exclusion chromatography (SEC) column has been recently introduced for efficient separation of mRNA aggregates and lipid nanoparticles. 20 Additionally, mass photometry (MP) was recently introduced as an interferometric mass spectrometry (MS) methodology capable of measuring the mass and relative abundance of biomolecules in solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, considerable efforts have been made to improve the separation, sensitivity, applicability, and turnaround times of the HPLC-based methods. For example, the choice of the IP-RPLC column, the composition of the mobile phase using an ion-pairing agent, and the column temperature have been studied for short 100-nt RNAs. , Regarding the analysis of long mRNAs, Kuwayama et al reported the interest in using an octadecyl-based RPLC column with superwide pores for achieving higher separation . Similarly, an ultrawide pore size exclusion chromatography (SEC) column has been recently introduced for efficient separation of mRNA aggregates and lipid nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…To separate short-stranded nucleic acids, numerous nucleic acid analysis studies employed various separation modes, e.g., the ion-exchange, RP, and hydrophilic interaction chromatography (HILIC) modes, [16][17][18][19][20] columns, 21,22 and mobile phases, e.g., mobile phases containing ion-pair reagents, such as triethylamine (TEA), N,N-diisopropylethylamine, and triethylammonium acetate. [23][24][25] However, only a few studies have considered the analyses of medium-and long-stranded nucleic acids. To ensure the widespread use of nucleic acid-based medicines, which are still being developed, the guidelines for analyzing the various chain lengths of their constituent nucleic acids of interest are required.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of n / n – x oligonucleotides, where x is the number of truncated nucleotides, is readily achievable for oligonucleotides up to 25 nucleotides long. A limited number of reports describe LC separation of >50 nt oligonucleotides, , while >100 nt species are extremely difficult to analyze with n / n – 1 resolution. , Separations of >100 nt single-stranded (ss) and double-stranded (ds) nucleic acids are described in the literature with IEX and IP RP LC; however, the resolution decreases with the nucleic acid length and does not afford n / n – 1 resolution. ,,, …”
mentioning
confidence: 99%
“…28,34 Separations of >100 nt single-stranded (ss) and double-stranded (ds) nucleic acids are described in the literature with IEX and IP RP LC; however, the resolution decreases with the nucleic acid length and does not afford n/n − 1 resolution. 12,13,35,36 Size exclusion chromatography (SEC) is a method that separates the compounds according to their size. 37 The technique is widely used for the analysis or purification of polymers and proteins.…”
mentioning
confidence: 99%